Analisa Peran Pelatihan dalam Meningkatkan Kinerja Karyawan: Kajian Literatur - Shofi Nur Fauziyah; Mudji Kuswinarno (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Organizations must be able to adapt and innovate to maintain their edge in the increasingly competitive era of globalization. Employee performance is a critical component that contributes to organizational success. An organized and sustainable job training program is one of the most effective methods. This research is a descriptive qualitative research, with a literature study approach to analyze the role of training in improving employee performance. The data sources in this study consist of various scientific articles, journals, books, and research reports that focus on the relationship between training and employee performance. The results show that employee training has a significant impact on individual and organizational performance. Based on the literature review conducted, there is a consensus that a structured and relevant training program can improve employees' skills, knowledge and motivation. By understanding the factors that influence training effectiveness, organizations can formulate more appropriate strategies to achieve desired business goals.